Radiocobalt theranostic applications: current landscape, challenges, and future directions - Sanwick, Alexis M.; Chaple, Ivis F. (Frontiers in Nuclear Medicine, 2025)
Radiocobalt-based theranostics has emerged as a promising platform in nuclear medicine that offers dual capabilities for both diagnostic imaging and targeted radionuclide therapy. 55Co (t1/2 = 17.53 h, β+ = 77%, Eγ = 931.1 keV, Iγ = 75%) and 58mCo (t1/2 = 9.10 h, IC = 100%) serve as an elementally matched pair for positron emission tomography and targeted Auger electron therapy, respectively, that enable a more personalized approach to cancer management, where imaging with 55Co can help to guide and predict therapeutic outcomes for 58mCo therapy. The unique coordination chemistry of cobalt allows for stable complexation with various chelators, enhancing in vivo stability and targeting efficacy when conjugated to biomolecules such as peptides, antibodies, and small molecules. Recent developments in radiolabeling techniques, chelator design, and preclinical evaluations have significantly improved the pharmacokinetic profiles and tumor specificity of radiocobalt-based radiopharmaceuticals. The aim of this mini review is to provide an overview of the recent advancements and applications of radiocobalt isotopes with a particular focus on the production, chelation chemistry, and in vivo targeting of 55Co- and 58mCo-labelled radiopharmaceuticals over the last 5 years. While challenges still exist in production scalability, dosimetry optimization, and clinical translations, the current trajectory suggests a growing role for radiocobalt-based theranostics in precision oncology.